Hubungan Aktifitas Fisik, Kebiasaan Merokok dan Hipertensi terhadap Penyakit Jantung Koroner : The Relationship between Physical Activity, Smoking Habits and Hypertension on Coronary Heart Disease - Sriwahyuni (MPI Press, 2023)
Introduction: The incidence of CHD at the Kalabahi Hospital has increased every year. In 2019, there were 568 CHD patients, and about 60% of the total CHD patients experienced complications of Kidney Failure, so they had to be hemodialyzed and had an impact on sudden death. Objectives: This study aims to determine the relationship of physical activity, smoking habits, and hypertension to coronary heart disease at the Kalabahi Hospital Polyclinic, Alor, East Nusa Tenggara, 2022. Methode: Type of analytical research with a cross-sectional approach. The sample in this study was 52 CHD patients undergoing outpatient treatment at the Kalabahi Regional Hospital Polyclinic. The sampling technique used in this research is Total Sampling. data collection techniques using questionnaires. Data analysis used the Pearson Product Moment statistical test and Multiple Correlations to determine the relationship between Physical Activity, Smoking Habits, and Hypertension in Coronary Heart Disease. Result: Based on the results of the analysis, it was found that the relationship between physical activity and coronary heart disease had a p-value of 0.000. The relationship between smoking habits and coronary heart disease has a p-value of 0.040 and the relationship between hypertension and coronary heart disease has a p-value of 0.000. Conclusion: There is a relationship between physical activity, smoking habits, and hypertension in coronary heart disease at the Kalabahi Hospital Polyclinic, Alor, East Nusa Tenggara, 2022.